Highly Sensitive Electromechanical Piezoresistive Pressure Sensors Based on Large-Area Layered PtSe2 Films - Wagner, Stefan; Yim, Chanyoung; Mcevoy, Niall; Kataria, Satender; Yokaribas, Volkan; Kuc, Agnieszka; Pindl, Stephan; Fritzen, Claus-Peter; Heine, Thomas; Duesberg, Georg S.; Lemme, Max C. (Nano Letters, 2018)
Two-dimensional (2D) layered materials are ideal for micro- and nanoelectromechanical systems (MEMS/NEMS) due to their ultimate thinness. Platinum diselenide (PtSe2), an exciting and unexplored 2D transition metal dichalcogenide material, is particularly interesting because its low temperature growth process is scalable and compatible with silicon technology. Here, we report the potential of thin PtSe2 films as electromechanical piezoresistive sensors. All experiments have been conducted with semimetallic PtSe2 films grown by thermally assisted conversion of platinum at a complementary metal-oxide-semiconductor (CMOS)-compatible temperature of 400 °C. We report high negative gauge factors of up to -85 obtained experimentally from PtSe2 strain gauges in a bending cantilever beam setup. Integrated NEMS piezoresistive pressure sensors with freestanding PMMA/PtSe2 membranes confirm the negative gauge factor and exhibit very high sensitivity, outperforming previously reported values by orders of magnitude. We employ density functional theory calculations to understand the origin of the measured negative gauge factor. Our results suggest PtSe2 as a very promising candidate for future NEMS applications, including integration into CMOS production lines.
CRIS-Team Scopus Importer:2022-04-14
Keywords: gauge factors; platinum diselenide; Pressure sensors; strain sensors; two-dimensional